2022
DOI: 10.1002/jsfa.11756
|View full text |Cite
|
Sign up to set email alerts
|

Fungal diversity and mycotoxins detected in maize stored in silo‐bags: a review

Abstract: Silo-bags are hermetic storage systems that inhibit fungal growth because of their atmosphere with low humidity, as well as low pH and O 2 concentrations, and a high CO 2 concentration. If a silo-bag with stored maize loses its hermetic nature, it favors the development of fungi and the production of mycotoxins. To the best of our knowledge, this is the first review on the diversity of fungal species and mycotoxins that were reported in maize stored under the environmental conditions provided by silo-bags. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 128 publications
(276 reference statements)
0
4
0
Order By: Relevance
“…Rice is one of most important food species in world, and about 50% of world's population consumes rice as a staple food, among which more than 2 billion people in Asia rely on rice and its products as main source of calorie intake [1] . For many years, China's rice production has ranked rst in world, accounting for about 30% of world's total rice production and about 1/3 of total domestic cereal production [2] . Rice in China is mainly used in four areas: feed, seed, edible and industrial, among which edible consumption is up to 80%, and its consumption is gradually increasing with improvement of people's living standard and increase of population [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Rice is one of most important food species in world, and about 50% of world's population consumes rice as a staple food, among which more than 2 billion people in Asia rely on rice and its products as main source of calorie intake [1] . For many years, China's rice production has ranked rst in world, accounting for about 30% of world's total rice production and about 1/3 of total domestic cereal production [2] . Rice in China is mainly used in four areas: feed, seed, edible and industrial, among which edible consumption is up to 80%, and its consumption is gradually increasing with improvement of people's living standard and increase of population [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on microbial diversity in seeds of different plants, e.g., maize (Brito et al 2022), orchid (Gao et al 2019), cauliflower (Dhekle et al 2013), cacao (de Araujo et al 2019) lima bean (Mota et al 2017), common bean (Parsa et al 2016), and rice (Fisher & Petrini 1992). Our study looked into the microbes associated with cherry tomato seeds.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, the articles that met the inclusion criteria for the current study did not offer a definitive picture regarding mycotoxin production differences in conventional and hermetic bags. However, a recent review and several studies that specifically evaluated the inhibitory effects of hermetic bags on mycotoxin formation strongly indicate that storage in hermetic bags is efficacious in preventing additional mycotoxin contamination 84,85 …”
Section: Discussionmentioning
confidence: 99%
“…However, a recent review and several studies that specifically evaluated the inhibitory effects of hermetic bags on mycotoxin formation strongly indicate that storage in hermetic bags is efficacious in preventing additional mycotoxin contamination. 84,85 Utility for smallholder farmers Despite these merits, the adoption of hermetic bags still remains low in most developing countries. 86,87 The initial cost of hermetic bags is considered to be one of the deterrent factors.…”
Section: Mycotoxin Contaminationmentioning
confidence: 99%